2009
DOI: 10.1080/09712119.2009.9707078
|View full text |Cite
|
Sign up to set email alerts
|

Effects of a Long Daily Photoperiod on Milk Yield and Ovarian Activity of Saanen Goats in Northern Mexico

Abstract: VBliz, F.G., Mellado, M., Carrillo, E., Meza-Herrera, C.A. and Rivas-Muiioz, R. 2009

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 11 publications
0
2
0
Order By: Relevance
“…The elements of the lactation pattern are the production peak (maximum milk yield during lactation) and the persistence, which indicates the animal's capacity to maintain a continuous milk production after the lactation peak (Cannas, Nudda, & Pulina, ; Salinas & Martínez, ). Just as with other species of ruminants, goat milk composition is affected by diverse factors, such as breed, individual characteristics, lactation stage, handling, climate, photoperiod, feed composition, as well as huge variations not only between but also within the production systems (Guo, Dixon, Park, Gilmore, & Kindstedt, ; Maroteau et al., ; Salinas‐González et al., ; Veliz, Mellado, Carrillo, Meza‐Herrera, & Rivas‐Muñoz, ). Therefore, it is necessary to know the composition of goat milk (fat [FT], protein [PR], lactose [LC], nonfat solids [NFS], and total solids [TS]) in order to identify not only feed strategies but also for opportune decision‐making, particularly in the critical seasons in natural rain‐fed production systems (Bedoya, Rosero, & Posada, ).…”
Section: Introductionmentioning
confidence: 99%
“…The elements of the lactation pattern are the production peak (maximum milk yield during lactation) and the persistence, which indicates the animal's capacity to maintain a continuous milk production after the lactation peak (Cannas, Nudda, & Pulina, ; Salinas & Martínez, ). Just as with other species of ruminants, goat milk composition is affected by diverse factors, such as breed, individual characteristics, lactation stage, handling, climate, photoperiod, feed composition, as well as huge variations not only between but also within the production systems (Guo, Dixon, Park, Gilmore, & Kindstedt, ; Maroteau et al., ; Salinas‐González et al., ; Veliz, Mellado, Carrillo, Meza‐Herrera, & Rivas‐Muñoz, ). Therefore, it is necessary to know the composition of goat milk (fat [FT], protein [PR], lactose [LC], nonfat solids [NFS], and total solids [TS]) in order to identify not only feed strategies but also for opportune decision‐making, particularly in the critical seasons in natural rain‐fed production systems (Bedoya, Rosero, & Posada, ).…”
Section: Introductionmentioning
confidence: 99%
“…New strategies are being developed to increase milk production without the use of hormones. Veliz et al (2009) used photoperiod manipulation and observed that increased post-partum photoperiod during winter months in northern Mexico substantially increased milk production in Saanen goats, which might constitute a management strategy for dairy goat producers to increase milk yield in Mexico. Mastitis is always a hot topic due to the milk yield reduction produced by intramammary infections (IMI).…”
Section: Milk and Cheese Production And Qualitymentioning
confidence: 99%